The value of board diversity in the relationship of corporate governance and investment decisions of Pakistani firms - Nauman Iqbal Mirza; Qaisar Ali Malik; Ch. Kamran Mahmood (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Inspired by the studies on the impact of diversity among decision-making groups, this study was carried out to examine whether the diversity of the members of the board of directors, encompassing gender, nationality, education, and experience, moderates the relationship between the corporate governance and investment decisions of listed companies of the Pakistan Stock Exchange. Furthermore, the determinants of investment decisions in the context of Pakistani firms' are also explored. Panel data analysis techniques are used to gauge the cause and effect relationship among the variables. We find short-term liquidity and profitability are the determinants of Pakistani firms' investment decisions, both having adverse relationships. Moreover, we explore board independence, and chief executive officer (CEO) duality has a significant positive impact on investment decisions. We further find that experience diversity strongly moderates the relationship between board independence and board size with investment decisions in the opposite direction. Education diversity moderates the relation of board size and investment decisions in the same direction. Foreign directors' presence on the board also significantly moderates the relationship between board independence and investment decisions. The results of this empirical study confirm that board diversity moderates the relationship between corporate governance and investment decisions.
Keywords: 650; capital budgeting; capital outlay decisions; corporate governance; education diversity; experience diversity; gender diversity; investment decisions; nationality diversity and board diversity